First report of Phytopythium vexans causing root rot on Macadamia integrifolia in China - Li, Yu Pin (Plant disease, 2023)
Soil-borne plant-pathogenic Phytopythium spp. can cause root rot and damping off on important plant species, resulting in serious economic loss. A survey in October 2021 identified soil-borne diseases occurring on Macadamia integrifolia in Yunnan Province, China. Microbes were isolated from necrotic roots of 23 trees with root rot symptoms by growing on cornmeal-based oomycete-selective 3P (Haas 1964) and P5APR (Jeffers and Martin, 1986) media at 24ºC in the dark for 7 days. Of the 56 single-hyphal isolates obtained, 18 were morphologically similar to Phytopythium vexans (van der Plaats-Niterink 1981; de Cock et al. 2015). Isolates LC04 and LC051 were selected for molecular analyses. The internal transcribed spacer (ITS) region and the cytochrome c oxidase subunit II (CoxII) gene were PCR-amplified using universal primers ITS1/ITS4 (White et al. 1990) and oomycete-specific primers Cox2-F/Cox2-RC4 (Choi et al. 2015), respectively. The PCR products were sequenced with the amplification primers and sequences were lodged in Genbank (Accession no. OM346742, OM415989 for ITS, OM453644, OM453643 for CoxII for isolates LC04 and LC051, respectively). The top BLAST hit in the Genbank nr database for all four sequences was Phytopythium vexans (>99% identity). A maximum-likelihood phylogenetic tree was constructed with analogous concatenated ITS and CoxII sequences from either type or voucher specimens of 13 Phytopythium species in the same phylogenetic clade as P. vexans (Table 1; Bala et. al 2010). Isolates LC04 and LC051 grouped most closely to P. vexans, with LC051 basal and sister to LC04 and P. vexans voucher specimen CBS119.80 with 100% support (Fig. 1). Millet seed inoculated with agar pieces colonized by P. vexans LC04 and LC51 was used to fulfill Koch's postulates (Li et al. 2015) in a completely randomized experimental design. Four 6-month-old M. integrifolia var. Keaau (660) seedlings were transplanted into pasteurized commercial potting mix containing 0.5% (w/w) inoculum. Plants were grown in free draining pots and watered once a day. At 14 days post-inoculation, roots were discolored compared to control plants inoculated with millet seed mixed with agar plugs lacking P. vexans (Fig. 2). By 30 days post-inoculation, infected roots were discolored with obvious decay and reduction in root system size. Control plants were symptomless. P. vexans was successfully re-isolated from two lesioned roots from each plant. The infection experiment was done twice, demonstrating that P. vexans LC04 and LC51 caused root disease on M. integrifolia. P. vexans causes root rot, damping-off, crown rot, stem rot or patch canker on economically important trees in many parts of the world, including seven plant species in China (Farr and Rossman 2022). This is the first report of pathogenic P. vexans on M. integrifolia in China. Reports of pathogenic P. vexans on multiple hosts in several parts of the world suggest it should be considered a quarantine risk and included in risk mitigation or pest management plans that include other species of Phytopythium, or species of Pythium or Phytophthora, to which P. vexans has many similarities (de Cock et al. 2015)